The Chat as a learning tool in the administration of a postgraduate course. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
This article describes the experiences gained during the management of the subject "fundamentals of environmental education", framed in the first semester of Postgraduate in environmental education of the UNELLEZ, co-managed with students of Acarigua -Araure. With the premise that the participants should handle important topics and must fix position in the matter, there were three (3) scheduled chat sessions and some conditions were established giving the following results: Chat 1: Permaculture, Agroecology and Endogenous Development; In the initial session was intended that participants will get familiar with the tool and would express their concerns on the subject, in 2 hours and 2 minutes 287 messages were sent among the 16 participants, 51% were about the topic content, 17% greeting and 32% trivial. Chat 2: global environmental problems, in 2 hours and 16 minutes 313 messages were sent among the 15 participants from which 52% were topic content, 13% greeting and 31% trivial. Chat 3: legislative and institutional framework for environmental education. The Chat 3 had a different condition than the previous two (2), in this case students had to build the teaching tool because there was no instructor present. In 2 hours the 15 participants sent 329 messages, 64% were content, 21% greeting and 15% trivial. The chat is a very useful tool for education at the university level; it allows you to have a clear position on a determined topic before a specific group; it is demanding
Keywords: environmental education; graduate; chat; teaching tool